Acoustic Breathiness Index for the Japanese-Speaking Population: Validation Study and Exploration of Affecting Factors - Hosokawa, Kiyohito; von Latoszek, Ben Barsties; Ferrer Riesgo, Carlos Ariel; Iwahashi, Toshihiko; Iwahashi, Mio; Iwaki, Shinobu; Kato, Chieri; Yoshida, Misao; Umatani, Masanori; Miyauchi, Akira; Matsushiro, Naoki; Inohara, Hidenori; et al. (Journal of Speech Language and Hearing Research, 2019)
Objectives The purposes of this study were to validate the Acoustic Breathiness Index (ABI) for the Japanese-speaking population and to determine whether it is independent of factors such as sex, age, and perceptual ratings of roughness. Method First, the concurrent validity of the ABI for perceptual breathiness was evaluated on the concatenations of continuous speech and sustained vowels from 288 patients with varying degrees of dysphonia. The diagnostic accuracy was examined on 343 samples with 55 additional normophonic speakers. Second, the validity related to responsiveness-to-change was estimated on 222 samples obtained before and after interventions for 111 voice-disordered patients. Third, the relationships between the ABI and other variables (i.e., perceptual hoarseness/breathiness/roughness, sex, and age) were explored using bivariate and multivariate analyses for the 288 patients. Results First, the concurrent validity and the responsiveness-to-change validity were confirmed by strong correlation coefficients of .890 and .878, respectively. Second, the receiver operating characteristic analysis showed the area under the curve to be 0.939, indicating excellent accuracy. The ABI of 3.44 exhibited a sensitivity of 76.3% and a specificity of 94.1%. Third, although bivariate analyses revealed a weak relationship between ABI and roughness and an ABI difference by age, multiple regression analyses showed a strong relation between only ABI and breathiness, without a meaningful contribution from roughness, sex, and age factors. Conclusion The study confirmed that the ABI is an accurate and specific tool to estimate breathiness levels in the Japanese-speaking population and neither roughness, sex, nor age significantly affects the ABI.
CRIS-Team Scopus Importer:2019-09-03

Collinearity and Sample Coverage Issues in the Objective Measurement of Vocal Quality: The Case of Roughness and Breathiness - Ferrer Riesgo, Carlos Ariel; Haderlein, Tino; Maryn, Youri; de Bodt, Marc; Nöth, Elmar (Journal of Speech Language and Hearing Research, 2018)
Purpose: The aim of the study was to address the reported inconsistencies in the relationship between objective acoustic measures and perceptual ratings of vocal quality. Method: This tutorial moves away from the more widely examined problems related to obtaining the perceptual ratings and the acoustic measures and centers in less scrutinized issues regarding the procedure to establish the correspondence. Expressions for the most common measure of association between perceptual and acoustic measures (Pearson’s r) are derived using a multiple linear regression model. The particular case where the multiple linear regression involves only roughness and breathiness is discussed to illustrate the issues. Results: Most problems reported regarding inconsistent findings in the relationship between given acoustic measures and particular perceptual ratings could be linked to sample properties not directly related to the actual relationship. The influential sample properties are the collinearity between the regressors in the multiple linear regression and their relative variances. Recommendations on how to rule out this possible cause of inconsistency are given, varying in scope from data collection, reporting, manipulation, and results interpretation. Conclusions: The problems described can be extended to more general cases than the exemplified roughness and breathiness sample’s coverage. Ruling out this possible cause of inconsistency would increase the validity of the results reported.
UnivIS-Import:2018-09-11:Pub.2018.tech.IMMD.IMMD5.collin

Improving ensemble averaging by epoch detrending in evoked potentials - Torres-Rodríguez, Idileisy; Ferrer Riesgo, Carlos Ariel; Velarde-Reyes, Ernesto; Taboada-Crispi, Alberto (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2019)
The objective of this work is to evaluate different detrending methods in the quality of auditory evoked responses. We compared the average responses obtained by simply removing the DC level and the linear trend, and also the estimated trends using polynomials and Fourier models up to the 8th order. Two quality measures were used to compare the results: The standard deviation ratio, as a measure of the signal-to-noise ratio, and the correlation coefficient between consecutive responses obtained under the same experimental conditions. The best results were obtained using a polynomial model of order 7.
CRIS-Team Scopus Importer:2019-08-13
Keywords: CCR; Detrending; Ensemble averages; Evoked potential; SDR